Pneumatic programmable superrepellent surfaces. Issue 1 (25th July 2022) - Hu, Songtao; Cao, Xiaobao; Reddyhoff, Tom; Ding, Xijia; Shi, Xi; Dini, Daniele; deMello, Andrew J.; Peng, Zhike; Wang, Zuankai
Abstract: Morphological transformation of surface structures is widely manifested in nature and highly preferred for many applications such as wetting interaction; however, in situ tuning of artificial morphologies independent of smart responsive materials remains elusive. Here, with the aid of microfluidics, we develop a pneumatic programmable superrepellent surface by tailoring conventional wetting materials (e.g., polydimethylsiloxane) with embedded flexible chambers connecting a microfluidic system, thus realizing a morphological transformation for enhanced liquid repellency based on a nature‐inspired rigid‐flexible hybrid principle (i.e., triggering symmetry breaking and oscillator coupling mechanisms). The enhancement degree can be in situ tuned within around 300 ms owing to pneumatically controllable chamber morphologies. We also demonstrate that the surface can be freely programmed to achieve elaborated morphological pathways and gradients for preferred droplet manipulation such as directional rolling and bouncing. Our study highlights the potential of an in situ morphological transformation to realize tunable wettability and provides a programmable level of droplet control by intellectualizing conventional wetting materials. Abstract : Morphological transformation of surface structures is an efficient way to in situ tune the wettability, which mainly relies on smart responsive materials. We develop a pneumatic programmable superrepellent surface by tailoring conventional wetting materials with the aid of microfluidics, showing an in situ morphological transformation for wettability tuning and droplet manipulation (directional rolling and bouncing).